Instruments for the assessment of disaster management among healthcare professionals: a scoping review - Elshami, Sara; Yakti, Ola; Mohamed Ibrahim, Mohamed Izham; Awaisu, Ahmed; Sherbash, Mohamed; Mukhalalati, Banan (Frontiers in Public Health, 2025)
ObjectivesThe recent disasters have highlighted the importance of healthcare professionals (HCPs) in aiding communities and maintaining consistent services, prompting a global reconsideration of disaster preparedness approaches. This scoping review aimed to identify and evaluate the psychometric properties of the available instruments that measure disaster preparedness and readiness among HCPs.MethodsA scoping review was conducted using five concepts: disasters, health personnel, preparedness, management, and questionnaire. Three databases were searched for studies published in English. The identified instruments were summarized according to disaster type, disaster management phase, measurement scope/context, and healthcare discipline. The psychometric properties were evaluated according to content validity, response process, internal structure, relation to other variables, and consequences.ResultsThe Emergency Preparedness Information Questionnaire (EPIQ) was the most commonly used instrument, while the Provider Response to Emergency Pandemic (PREP) and the Korean version of the Disaster Preparedness Evaluation Tool (DPET) were the most valid instruments. Most instruments have undergone limited psychometric evaluations, primarily focusing on content and internal structure validations, with response process, relation to other variables, and consequences not frequently reported.ConclusionThe review highlights the lack of well-developed assessment instruments for disaster preparedness in healthcare disciplines, highlighting the need for future research to develop and thoroughly validate such instruments.Systematic review registrationhttps://www.researchregistry.com/browse-the-registry#registryofsystematicreviewsmeta-analyses/registryofsystematicreviewsmeta-analysesdetails/638dbba71e82b30021c02680/.